Bone Tissue Engineering Using Human Cells: A Comprehensive Review on Recent Trends, Current Prospects, and Recommendations - Saeid Kargozar; Masoud Mozafari; Sepideh Hamzehlou; Peiman Brouki Milan; Hae-Won Kim; Francesco Baino (Applied Sciences, 2019)
The use of proper cells for bone tissue engineering remains a major challenge worldwide. Cells play a pivotal role in the repair and regeneration of the bone tissue in vitro and in vivo. Currently, a large number of differentiated (somatic) and undifferentiated (stem) cells have been used for bone reconstruction alone or in combination with different biomaterials and constructs (e.g., scaffolds). Although the results of the cell transplantation without any supporting or adjuvant material have been very effective with regard to bone healing. Recent advances in bone scaffolding are now becoming new players affecting the osteogenic potential of cells. In the present study, we have critically reviewed all the currently used cell sources for bone reconstruction and discussed the new horizons that are opening up in the context of cell-based bone tissue engineering strategies.